The Potential of Ethanol Extract from Langsat Leaves (Lansium Domesticum Var. Pubescent) In Controlling Aedes Aegypti Mosquitoes: A Study on The Effectiveness of Natural Substances as Mosquito Repellents - Ukratalo, Abdul M; Ichsan, Muhammad Nurhidayat; Kaihena, Martha; Manery, Dodikrisno Ekaputra; Pangemanan, Victory Osvaldo; Moniharapon, Debby Dijola (Universitas Karya Husada Semarang, 2024)
In recent decades, attention to the utilisation of natural materials as alternatives in vector control has increased. One potential source that needs to be explored is langsat leaves, which are known to have active compounds. Ethanol extracts of langsat leaves may contain compounds that can provide control effects against Aedes aegypti mosquito larvae. This study aims to assess the effectiveness of the ethanol extract of langsat leaves in controlling Aedes aegypti mosquitoes, the vector of Dengue Fever disease. The extraction method was carried out using the maceration technique with ethanol as the solvent. Bioactivity test was conducted through larvicidal bioassay against Aedes aegypti larvae. The results showed that the ethanol extract of langsat leaves has a larvicidal effect against Aedes aegypti mosquito larvae. The toxicity levels, both LC50 and LC90, indicate that the ethanol extract of langsat leaves has potential as a mosquito larva control agent.